PENANAMAN NILAI SPORTIVITAS PADA ANGGOTA PENCAK SILAT KELABENGAN MADURA DI DESA SUNGAI RENGAS - Rudi, Rudi; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "Planting Sportsmanship Value on Madura Centipede Pencak Silat Members in Sungai Rengas Village". The general problem in this research is how to Plant Sportivity Values on Members of Centipede Pencak Silat in Sungai Rengas Village? The first sub-problem is the value of sportsmanship, both the implementation process, the three obstacles and solutions. The purpose of the study was to find out the value of sportsmanship in members of centipede pencak silat. Common problems in this study are how to invest in sportsmanship values for members of centipede pencak silat. The approach used in this study is a qualitative approach. By using informants as much as 5. The results of this study indicate that the planting of sportsmanship values in the members of pencak silat is in existence, devoted to Allas Swt, brotherhood, honesty, mutual help, and responsiveness followed by the second sub namely night, the third sub namely rain resistance, and the fourth sub in the house.        Keywords: Planting, Value, Sportivity, Members of Pencak Silat